Evaluation of Efficacy, Efficiency, and Cell Viability of a Novel Descemet Membrane Endothelial Keratoplasty Graft Preparation Device, DescePrep, in Nondiabetic and Diabetic Human Donor Corneas. Issue 4 (5th April 2022) - Solley, Katherine D.; Berges, Alexandra; Diaz, Christine; Ostrander, Benjamin T.; Ding, Andy S.; Larson, Sara A.; Frank, Kendall; Lee, Darrell; Guerrero, Juan; deCarvalho, Tagide; Ruppel, Edward; Haileyesus, Ailon; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to evaluate the safety, efficacy, and efficiency of a Descemet membrane endothelial keratoplasty (DMEK) graft preparation device, DescePrep, through measurement of graft viability, yield, and preparation time in both healthy and diabetic (high-risk) donor eyes. Methods: Twenty nondiabetic and 10 diabetic donor corneas were processed using DescePrep, which standardizes the liquid bubble technique. Corneas were stained with trypan blue and then processed. Cell counts through specular microscopy, optical coherence tomography imaging, and slit-lamp analysis were used for the evaluation of graft separation and viability in 5 nondiabetic corneas. The remaining 25 corneas (15 nondiabetic and 10 diabetic) were evaluated for preparation success rate and processing time. Ten corneas (5 nondiabetic and 5 diabetic) were randomly selected for further evaluation of global cell loss through staining. Results: Ninety-seven percent of corneas (29 of 30) were prepared successfully with DescePrep. The average preparation time was 2.83 ± 1.8 minutes. There was no significant difference in the time of preparation between the nondiabetic and diabetic groups ( P = 0.077). The overall average cell death after processing was 7.9% ± 3.7% for all corneas. There was no significant difference in cell viability between diabetic and nondiabetic tissues after DescePrep processing ( P = 0.769). Conclusions: DescePrep is a new DMEK preparation technique that can process both nondiabetic and diabetic donor corneas at high yields in minutes. High-yield preparation of diabetic corneas may offer eye banks access to a larger donor pool, which is important because the demand for DMEK grafts continues to rise worldwide.